Natural Antioxidant Extracts as Anti-browning Agents from Algerian Date Palm Fruit - Wafa, Bensania; Amar, Djeridane; Noureddine, Bouras; Mohamed, Yousfi (Current Enzyme Inhibition, 2024)
Enzymatic browning is a negative change that affects fruits and vegetables. This makes them unfit for consumption or reduces their shelf life and quality. This reaction alters the appearance, texture, fragrance, taste, and nutritional value of the food. In order for these products to be widely accepted by consumers, it is necessary to use natural compounds with anti-browning properties. Objective The main objective of this study was to select effective extracts for the anti-browning (anti-polyphenol oxidase and anti-peroxidase), and antioxidant activities of by-products of Phoenix dactylifera L., Ghars variety, from Algeria. Methods Hydro-methanolic extracts from the pedicel, perianth, and leaves of date palm were examined to evaluate the phenol and total flavonoid contents. Using spectrophotometric techniques, the antioxidant activities were assessed using 1, 1-diphenyl-2-picrylhydrazyl radical (DPPH●), 2, 2’-azino-bis-(3-ethylbenzthiazoline-6-sulfonic acid) radical (ABTS●+) and Ferric Reducing Antioxidant Power (FRAP) assay, examined the enzyme inhibitory activity against polyphenol oxidase and peroxidase of Phoenix dactylifera L. extract. Results The range of total phenolic and flavonoid contents was 12.29 to 48.98 mg gallic acid equivalent/g dry matter and 2.83 to 15.07 mg rutin equivalent/g dry matter, respectively. The pedicel extracts showed significant antioxidant activity in the DPPH and FRAP tests (IC50 = 0.0057 ± 0.0010 mg/ml and FEAC = 1.1961 ± 0.0647) compared to other extracts. However, in the ABTS assay, the leaf extract exhibited an interesting potency (IC50 = 0.0020 ± 0.0001mg/ml). The study on the anti-browning activity of date palm by-product extracts showed that it inhibited the activity of peroxidase enzyme from date palm fruit. Conclusion This work is the first time the potential of an extract from date palm by-products to enzymatically reduce the browning of date palms is presented. According to the results obtained, the different organs studied from the Ghars date palm, are a powerful natural antioxidant and may include natural compounds that retard browning by enzymes.
Keywords: antioxidant activity